Polysemy and cognitive linguistics. The case of vána - Jurewicz, Joanna (Lingua Posnaniensis, 2019)
The aim of this paper is to address the problem of the polysemy of Sanskrit words using the example of the meanings of the word vána used in the Ṛgveda (“a tree, wood, forest, fire drill, vessel for Soma, water and material of the world”). I will show that the methodology of cognitive linguistics is very useful to analyse the rational background of polysemy and its conceptual consistency. The basis for my analysis is three assumptions accepted in cognitive linguistics: 1. the meaning of words reflects thinking about the designate; 2. thinking is motivated by experience and cultural beliefs; 3. the associations between semantic aspects of the word can be modelled as conceptual metonymy, conceptual metaphor and conceptual blending. On the basis of these assumptions, I will reconstruct the semantic structure of the word vána. It is a radial category, the centre of which is constituted by its most literal meaning, “tree”, and its metonymic extensions, i.e. wood and forest. The meanings of things made of wood (i.e. fire drill and vessel) are also close to the central meaning and are metonymic extensions. The meanings of water and the material of the world are metaphoric extensions of the central meaning and more peripheral. They are based on cultural beliefs and models shared by the Ṛgvedic poets. I will also argue that the Ṛgvedic poets consciously shaped the semantics of the word vána by using it in contexts which forced the recipient to activate its less literal meanings. Thus they could create a general concept of the hiding place of desirable goods, such as fire, Soma, the sun, and the world.